2006
DOI: 10.1002/adma.200600303
|View full text |Cite
|
Sign up to set email alerts
|

A Mechanism for the Fast Ionic Transport in Nanostructured Oxide‐Ion Solid Electrolytes

Abstract: Ionic transport in nanostructured solid electrolytes is investigated using an atomistic model that clarifies the enhanced conductivity (see figure) of these materials. It is based on the fast diffusion of free oxygen vacancies through the grain boundaries. A transition observed in the ionic conductivity of the nanoceramics as a function of temperature, caused by a change in the transport mechanism, is also explained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(61 citation statements)
references
References 39 publications
1
60
0
Order By: Relevance
“…It cannot be fitted with a single straight line, because of the nano-crystalline nature of the material. Two different straight lines -one in low temperature region and the other in high temperature region -are needed to fit the curve [19,20] shown in Figure 7. The oxide ionic conductivity is found to increase with increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…It cannot be fitted with a single straight line, because of the nano-crystalline nature of the material. Two different straight lines -one in low temperature region and the other in high temperature region -are needed to fit the curve [19,20] shown in Figure 7. The oxide ionic conductivity is found to increase with increase in temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Recent developments are directed by extensively using nanotechnology and nano-size materials for the conventional SOFC electrolytes and support new scientific principles. These new studies from nano-aspects have shown the common facts that the nanostructured ceria-based materials [12][13][14][15] and YSZ [16,17] exhibited strong conductivity enhancement, due to significantly larger area of grain-boundary or interface in nanostructured systems, which increases the concentration of mobile defects in the space-charge zone [9,10]. The grain-boundary in ionic conduction suddenly turns from negative/side effect in the normal-sized (say micrometer level) to positive effect as promoter in the nano-sized materials.…”
Section: Nano-effects and New Principlesmentioning
confidence: 97%
“…Nanostructured solidstate ionic electrolyte, coined as 'nanoionics' [8,9], has recently become one of the hot areas of research related to nanomaterials, since they can be used in advanced energy conversion and storage applications [10], for example SOFCs [11][12][13][14][15][16][17]. A more effective way is to develop new materials with improved performance, for example superionic conduction at LT, say 0.1 S cm À1 at 300-6001C [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The ongoing research is focused on the optimization of the ionic conductivity of these materials, which is usually done either by chemical substitutions or controlling of the synthesis and sintering conditions. Nanostructured ionic materials (nanoionics) with particle size less than 50 nm have greatly enhanced ionic conductivity compared to their coarse grained counterparts due to the fast ion transport along their interfacial regions that comprise both grain boundaries and surfaces [16][17][18][19][20][21][22]. The interfaces in nanoionics provide diffusion pathways with low activation energy for the hopping ions, leading to the enhanced ionic conductivity [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 98%